Determinants of intention to buy counterfeit product / Rabi’atuladawiyah Mohd Sharun - Mohd Sharun, Rabi’atuladawiyah (2014)
Determinants of intention to buy counterfeit product is a study about factors that affect counterfeit purchase intention. In the situation keep improving, counterfeit products are mushrooming in the market. In Malaysia, demands for counterfeit products are too high. We can see it in the night market, in a shop, in a shopping center not only in rural market but also in urban market. There are three variables that the researcher wants to examine the relationship towards counterfeit purchase intention. Socio-cultural factors, attitude towards economic benefit, and past purchase experience. Basically, people buying counterfeit because of someone influence, price and have the experience on buying counterfeit. But, which factors is most influence consumer to buy counterfeit? In this research, the researcher decides to study about Kota Tinggi, Johor people about their intention towards counterfeit. Since Kota Tinggi have many estates and Felda, that consider rural area, and there also have urban area, and from the observation, majority of people in Kota Tinggi people salary not exceed high level of income, the researcher think this is the best location to finished this research. The questionnaire was distributes to 140 people that live in urban and rural area, that their salary is between low level income and medium level income. From the results, the researcher found that only 2.9% of them that not have experience on buying counterfeit. From the data collected, all the variables are reliable and significant, all the hypotheses are accepted and attitude toward economic benefit is the most significant variable that affects the counterfeit purchase intention.